Kesiapan Pengguna Rekam Medis Elektronik (RME) dengan Technology Readiness Index (TRI): Studi Kasus di RSUD DAHA HUSADA - Budi Pranoto; Anggia Dini Panggabean; Eva Firdayanti Bisono (STIKES Columbia Asia Medan, 2026)
The readiness of officers to carry out Electronic Medical Records (RME) needs to be measured using the Technology Readiness Index (TRI) method, which is an index used to measure the readiness of new technology users to achieve goals in daily life and work. This research aims to determine the readiness of Electronic Medical Record (RME) users using the Technology Readiness Index (TRI) case study at Daha Husada Regional Hospital. This is a descriptive research with an evaluation study where the research subjects are the head of medical records and 3 medical records officers in the inpatient registration section at Daha Husada Regional Hospital using a total saturated sampling technique. Data collection uses interview techniques. Data presentation is presented using narrative. The results of the research show that of the 4 variables used to measure the readiness of medical record users, medical record officers at Daha Husada Regional Hospital are ready to use medical records, even though they are ready there are still difficulties experienced and feelings of insecurity when using Electronic Medical Records (RME), namely Medical records can be accessed anywhere and are not yet integrated according to the user's wishes. Therefore, Daha Husada Regional Hospital should further tighten its electronic medical record data security system.